Detection of Porosity in Impregnated Die-Cast Aluminum Alloy Piece by Metallography and Computer Tomography - Mihály Réger; József Gáti; Ferenc Oláh; Richárd Horváth; Enikő Réka Fábián; Tamás Bubonyi (Crystals, 2023)
The porosity of die-cast aluminum alloys is a determining factor for the quality of the product. In this paper, we studied the porosity of a selected part of a die-cast AlSi9Cu3(Fe) compressor part by computer tomography and metallography. In the case of this part, the achievable resolution by CT, a non-destructive testing method, was 30 μm—this method could not detect smaller cavities. Based on metallographic analysis, the percentage of defects larger than 30 μm ranges from 10 to 30% of the total number of defects, which represents 75–95% of the defective area (area ratio). Impregnation with methacrylate resin (used to seal cavities to prevent leakage) can be detected with UV-illuminated optical microscopic examination on metallographically prepared specimens. As confirmed by scanning electron microscopy, partial filling and partial impregnation can occur in a system of shrinkage cavities.